Upaya Meningkatkan Kompetensi Profesional Guru Di SMP Muhammadiyah Waipare Kabupaten Sikka - Safrudin, Vitalia Rahmawati; Anshory, Ichsan (Program Studi Magister Pedagogi, 2018)
Abstract: One of the competency standards that must be possessed by a teacher is professional competency. In reality, there are still teachers who lack professional competency. The purpose of this study is to determine 1) the factors that influence the professional competence of teachers in Muhammadiyah Waipare Middle School. 2) Efforts are made in improving the professional competence of teachers in Muhammadiyah Waipare Middle School. The method used in this research is descriptive qualitative. Informants in the study were teachers, principals, vice-principals in student fields, school treasurers. Data collection uses observation, interview, and documentation techniques. The results of this study indicate that 1) factors influencing teacher professional competence include difficulties in delivering teaching material, internal factors, availability of facilities and infrastructure, teachers who are often not on time, lack of teacher welfare. 2) Efforts made to improve the professional competence of teachers in Muhammadiyah Waipare Junior High School are to increase the number of reference books, provide opportunities for teachers to continue to higher levels of education, Add infrastructure, provide opportunities for teachers to take part in MGMP workshop activities, and increase teacher welfare.Keywords: Professional Competency, Teachers, Secondary EducationÂ Abstrak: Standar kompetensi yang harus dimiliki oleh seorang guru salah satunya adalah kompetensi profesional. Pada kenyataannya masih ada guru yang kurang menunjukkan kompetensi profesional. Tujuan penelitian ini yaitu untuk mengetahui 1) faktor-faktor yang mempengaruhi kompetensi profesional guru di SMP Muhammadiyah Waipare. 2) Upaya yang dilakukan dalam meningkatkan kompetensi profesional guru di SMP Muhammadiyah Waipare. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Informan pada penelitian adalah Guru, Kepala sekolah, wakil kepala sekolah bidang kesiswaan, bendahara sekolah. Pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa 1) faktor yang mempengaruhi kompetensi profesional guru meliputi kesulitan dalam menyampaikan materi ajar, faktor internal, ketersedian sarana dan prasarana, guru yang sering tidak tepat waktu, kurangnya kesejahteraan guru. 2) Upaya yang dilakukan dalam meningkatkan kompetensi profesional guru di SMP Muhammadiyah Waipare yaitu dengan menambah jumlah buku referensi, memberikan kesempatan kepada guru untuk melanjutkan ke jenjang pendidikan yang lebih tinggi, Penambahan sarana prasarana, memberikan kesempatan kepada guru untuk mengikuti kegiatan workshop MGMP, dan meningkatkan kesejahteraan guru.Kata kunci: Komepetensi Profesional, Guru, Pendidikan Menengah